Managing drilling mud weight using ilmenite - Ismail, Issham; Ismail, Abdul Razak; Yang, Juhari (Faculty of Engineering, UPM, 1999)
Drilling mud plays an important role when drilling an oilwell, where it produces sufficient hydrostatic pressure that could prevent the influx of formation fluids into the wellbore. Barium sulphate, which is more commonly known as barite in the petroleum industry, is the principle weighting material used to increase mud weight. With the expected increase drilling activities and dwindling reserves, quality barite supply may fall short in the foreseeable future. Ilmenite, an iron-based mineral, is being investigated by the Drilling Fluid Research team of UTM of it’s potential to be used as an alternative weighting material. The study involved of laboratory experiments and amongst the parameters studied were mud mud weight/ density, rheological properties of drilling mud with all weighting materials, and the abrasiveness effect. Experimental results reveal that even though ilmenite is found to be more abrasive than barite, but it has the potential to substitute barite as weighting material. Two significant advantages could be realized via ilmenite; it produces lower solids content and fluid loss which in turns increases rate of penetration but reduces formation damage respectively.